The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-18462007000400013
|View full text |Cite
|
Sign up to set email alerts
|

A afecção vestibular infantil: estudo da orientação espacial

Abstract: OBJETIVO: verificar como é a percepção do espaço na criança com vertigem periférica. MÉTODOS: estudo prospectivo de 18 crianças, com faixa etária de três a 15 anos, sob acompanhamento no Ambulatório de Otorrinolaringologia / Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo. A percepção espacial foi avaliada por meio de atividade livre (desenho livre) e dirigida (blocos lógicos e teste de Frostig). Das 18 crianças avaliadas, nove constituíram o grupo estudo (diagnóstico de vestibulopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…It is believed that otoneurological evaluation can become a more efficient instrument in the evaluation and possible diagnosis in these children, and may also aid in speech-language intervention 5,21 , which, from the otoneurological results, can focus on activities that train notions of laterality and space, in addition to reading and writing, or even the joint activities. Therefore, it is suggested that this subject be approached in future studies, as the national literature investigating the evaluations of vectoelectronystagmography in children with dyslexia and learning disorders is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that otoneurological evaluation can become a more efficient instrument in the evaluation and possible diagnosis in these children, and may also aid in speech-language intervention 5,21 , which, from the otoneurological results, can focus on activities that train notions of laterality and space, in addition to reading and writing, or even the joint activities. Therefore, it is suggested that this subject be approached in future studies, as the national literature investigating the evaluations of vectoelectronystagmography in children with dyslexia and learning disorders is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as in adults, children may also present progressive or chronic loss of vestibular function that affects the development of postural control (2) . However, there is difficulty in diagnosing vestibular dysfunction in childhood, due to the variety of symptoms presented, and by the difficulty with reporting them (4) . Researchers (2) have made reference to Epidemiological studies with school-age children, which have shown that around 15% had experienced at least one episode of dizziness during the period of one year.…”
Section: Introductionmentioning
confidence: 99%
“…O protocolo de RV de Cawthorne e Cooksey é sugerido por ser de fácil aplicação e por permitir sua realização em grupo ocasionando assim, uma maior interação entre os pacientes [20][21][22][23] .…”
unclassified